2019
DOI: 10.1159/000499381
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the Current Risk Factors of Appendiceal Neuroendocrine Neoplasms: Can They Accurately Predict Local Lymph Nodal Invasion? Results from a Large Case Series

Abstract: Background: Appendiceal neuroendocrine neoplasms (ANEN) are uncommon entities, which run mostly an indolent course. Appendicectomy alone is usually curative, except for in a selected group of patients that are deemed to be at risk of loco-regional metastases, in whom a completion right hemicolectomy (RHC) is recommended. The current “Guidelines” criteria for the latter have been controversial, and may result in overtreatment, which is concerning for a young patient population. Objective: The aim of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 24 publications
0
48
0
2
Order By: Relevance
“…We identified seven studies reporting LN status at RHC for tumour size cutoffs of 10 and 20 mm [3,[11][12][13][14][15][16]. The rate of LN metastases for a cutoff size >10 mm was 48.6% (vs 12.1% for lesions <10 mm) among adult patients, with a random-effects OR of 4.8 (95% CI, 1.5-15.8; heterogeneity, P = 0.061; I 2 = 46.3%, Egger's p-value = 0.093, Fig.…”
Section: Pooled Results For Primary Tumour Sizementioning
confidence: 99%
“…We identified seven studies reporting LN status at RHC for tumour size cutoffs of 10 and 20 mm [3,[11][12][13][14][15][16]. The rate of LN metastases for a cutoff size >10 mm was 48.6% (vs 12.1% for lesions <10 mm) among adult patients, with a random-effects OR of 4.8 (95% CI, 1.5-15.8; heterogeneity, P = 0.061; I 2 = 46.3%, Egger's p-value = 0.093, Fig.…”
Section: Pooled Results For Primary Tumour Sizementioning
confidence: 99%
“…For tumor size 10–20 mm, various histopathological parameters have been applied to identify right candidates for completion pRHC although not fully validated. In particular, the location of the primary tumor in the base of the appendix, grade 2, mesoappendix, vascular, lymph vessel, and perineural invasion has been implied as a risk factors for synchronous LN metastases necessitating completion pRHC [ 7 , 8 , 13 , 27 , 28 ]. However, these factors were not confirmed in our study with respect to LN metastases prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary guidelines suggest a rather aggressive surgical approach with completion pRHC as a treatment option for patients diagnosed with tumors ≥20 mm or tumors 10–20 mm in the presence of certain histopathological parameters [ 5 , 6 ]. However, recent cohort studies and meta-analyses have questioned the validity of currently applied criteria for completion pRHC in WD-ANENs [ 2 , 7 10 ]. Nevertheless, the association of indolent locoregional lymph node (LN) metastases with long-term patient outcomes has not been fully determined [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prognostic impact of clinical and pathological parameters in NETs has been more extensively investigated, but a great variability of results is observed with special reference to the identification of independent factors when tested at multivariable analysis. In a recent study, size > 15 mm, presence of lympho-vascular invasion and G2 grade have been identified as independent indicators for the presence of lymph node metastases 6 , but only the latter two were identified in a similar study 7 and neither tumor grade nor tumor size were associated with disease-related survival in another study 8 . All these discrepancies reflect the high heterogeneity of study planning and case selection, which are the major biases of retrospective studies and are the cause of different indications to surgical treatment in different national and international guidelines.…”
Section: Neuroendocrine Neoplasms Of the Appendixmentioning
confidence: 96%